Castañeda and his Guises : Essays on the Work of Hector-Neri Castañeda - Palma, Adriano, 1956- (Walter de Gruyter Inc., 2014)
This volume responds to and reassesses the work of Hector-Neri Castañeda (1924-1991). The essays collected here, written by his students, followers, and opponents, examine Castañeda's seminal views on deontic logic, metaethics, indedicality, praticitions, fictions, and metaphysics, utilizing the critical viewpoint afforded by time, as well as new data, to offer insights on his theories and methodology.
Conference proceedings.
Keywords: Castañeda, Hector-Neri, -- 1924-1991 -- Congresses.; Castañeda, Hector-Neri, -- 1924-1991; PHILOSOPHY -- History & Surveys -- Modern.; Conference papers and proceedings